ANALISIS PRODUK BINAR GO MENGGUNAKAN PRIORITIZATION MATRIKS EISENHOWER DAN MODEL KANO - Renisa Nur Kamelia Putri; Dian Permata Sari; Rian Andrian (JURNAL ILMIAH BETRIK, 2022)
Edutech startups are currently experiencing rapid development. This is because Indonesia's need for digital skilled workers reaches 9 million people in 2030. One way to be able to print digital skilled workers is to facilitate learning according to industry needs. One of the edutech startups whose goal is to produce quality young people is Binar Academy. Various courses are provided at varying prices. The courses available at Binar Academy are Product Management, Frontend, Backend, Android Developer, UI/UX Designer and others. One of the newest products, Binar Go, provides interesting and flexible learning according to the needs of today's young generation. The Binar Go product in the product management course has a huge opportunity to increase digital skilled workers. Especially for the younger generation who will enter the industrial world. This research uses mixed methods, namely quantitative and qualitative methods. In a survey conducted, 55% of users said there were several obstacles when using the Binar Go android application that caused users to feel uncomfortable. To solve these problems, it is necessary to improve the product, one of which is by creating new features. Therefore, the researcher uses the prioritization of the Eisenhower Matrix and the Kano model in determining the priority of features that can increase user comfort when using the Binar Go product. The Eisenhower matrix is ​​a way that can be done in determining the priority of a job, while the Kano model is a diagram that can help prioritize consumer needs in more detail. By using the prioritization of the Eisenhower Matrix and the Kano model, 3 main features are obtained, namely the Search Bar feature, the Save Material feature, and the Black Mode feature. These features must be developed immediately to be able to increase user convenience in making purchases on Binar Go products on the Binar Academy Android Application.